Vejrforholdene i Landbrugsaaret 1907—08. (Fra 1. Oktober 1907 til 30. September 1908.) - Willaume-Jantzen, V. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1907—08. (Fra 1. Oktober 1907 til 30. September 1908.)